Pengaruh Dimensi Kualitas Layanan terhadap Kepuasan Pemustaka di Perpustakaan Daerah Kabupaten Labuhan Batu - Imam, Chairul; Ritonga, Sakti; Riza, Faisal (Medan Resource Center, 2024)
The study aims to analyze the influence of service quality on user satisfaction in the context of library services. Service quality is an essential aspect of the interaction between the library and its users. This research adopts a quantitative approach, involving 100 respondents as the sample. The data were analyzed using descriptive statistical techniques. The findings indicate that service quality significantly affects user satisfaction at the Labuhanbatu District Library and Archives Service. The study measured this effect through several key factors, including (1) Tangibility (physical aspects), (2) Reliability, (3) Responsiveness, (4) Assurance, and (5) Empathy. These factors collectively contribute to the users' satisfaction with the services provided by the Labuhanbatu library. The study highlights the importance of these dimensions in ensuring high-quality library services and improving user experience.